2016
DOI: 10.7717/peerj.2657
|View full text |Cite
|
Sign up to set email alerts
|

Salinity modulates thermotolerance, energy metabolism and stress response in amphipodsGammarus lacustris

Abstract: Temperature and salinity are important abiotic factors for aquatic invertebrates. We investigated the influence of different salinity regimes on thermotolerance, energy metabolism and cellular stress defense mechanisms in amphipods Gammarus lacustris Sars from two populations. We exposed amphipods to different thermal scenarios and determined their survival as well as activity of major antioxidant enzymes (peroxidase, catalase, glutathione S-transferase) and parameters of energy metabolism (content of glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…Our previous study (Vereshchagina et al, 2016) found elevated levels of antioxidant enzyme activity for catalase and glutathione S-transferase in saltwater G. lacustris when compared to the freshwater population. These high levels suggest higher constitutive levels of NCSR in cells; however further research is required to confirm the causes of the observed differences.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Our previous study (Vereshchagina et al, 2016) found elevated levels of antioxidant enzyme activity for catalase and glutathione S-transferase in saltwater G. lacustris when compared to the freshwater population. These high levels suggest higher constitutive levels of NCSR in cells; however further research is required to confirm the causes of the observed differences.…”
Section: Discussionmentioning
confidence: 86%
“…In concentrations over 4 mM (Fregoso-Peñuñuri et al, 2017), pyruvate is capable of inhibiting the enzyme activity in crustaceans. In another study, we demonstrated the elevation of adenosine triphosphate (ATP) and the depletion of glucose content in the first phases of exposure to gradual temperature increase when starting from 13 °C (Vereshchagina et al, 2016). This also denotes the activation of glucose oxygen catabolism.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations